Integrated Science Learning Webbed Type in Permaculture Theme and BRADeR Model to Enhance Science Literacy Competence of Junior High School Students - Syaifullah Syaifullah; Fida Rachmadiarti; Beni Setiawan; Edi Suwandi (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This research aims to assess the scientific literacy of State Junior High School 1 Ngoro students in integrated science learning using the webbed type with a permaculture theme and the BRADeR model. Method: This descriptive quantitative study involves 80 students from State Junior High School 1 Ngoro: 16 from class IX-A (limited trial) and 64 from IX-B and IX-C (broader trial). Data collection was conducted using a science literacy competence test instrument consisting of 10 essay questions designed according to three dimensions of scientific literacy proficiency. The validity assessment by three experts showed that 9 out of 10 questions scored an average of 4, categorizing them as "very valid," while 1 question was also deemed "very valid." The reliability assessment using Cronbach's Alpha indicates good dependability. Data analysis utilized inferential statistics to assess the viability of webbed-type integrated science learning on permaculture and the BRADeR model in improving students' science literacy. Results: Findings indicate a notable enhancement in science literacy, presenting a mean n-gain of 0.73, which is categorized as high. The most significant enhancement was in articulating scientific phenomena, next was experimental design and data analysis. A moderate enhancement was observed in investigating, applying, and evaluating scientific knowledge for decision-making. Novelty: This research examines improvements in science literacy and emphasizes the need for multimedia and multimodel approaches through integrated science learning using the webbed type and BRADeR model.